The integration of artificial intelligence in education: opportunities and challenges - Lampou, Rania (Review of Artificial Intelligence in Education, 2023)
Objective: To explore the current and potential role of Artificial Intelligence (AI) in the educational sector, addressing its benefits and potential challenges. Method: A comprehensive review of the existing literature and applications of AI in various fields, with a specific focus on its implications for education. Results: AI has seamlessly integrated into various aspects of our daily lives, from automated systems in vehicles to personalized online advertisements. In the realm of education, AI promises to enhance the teaching and learning experience. It aims to supplement, not replace, educators by making the learning process more engaging and efficient. AI systems can provide feedback on student performance, highlighting areas of improvement, and ensuring inclusivity for students with special needs or language barriers. Additionally, AI can automate many administrative tasks, allowing educators more time for lesson planning and instructional improvement. Conclusions: While AI presents numerous advantages for the educational sector, its integration should be approached with caution. Both educators and students need preparation for this technological shift to maximize its benefits and mitigate potential challenges. Implications: The onus is on governments, educational institutions, and related organizations to facilitate the smooth integration of AI in education. Proper training and awareness are essential to ensure that AI is utilized responsibly and effectively in educational settings.